Biscuit, cookie and cracker manufacturing manuals. Manual 2 : Biscuit doughs - Manley, Duncan (Woodhead Publishing Limited, 1998)
This manual describes the various types of biscuit dough, the key stages in dough mixing and handling, and identifies potential problem areas and solutions.